2012
DOI: 10.1021/ja208940u
|View full text |Cite
|
Sign up to set email alerts
|

Direct Carbonization of Al-Based Porous Coordination Polymer for Synthesis of Nanoporous Carbon

Abstract: Nanoporous carbon (NPC) is prepared by direct carbonization of Al-based porous coordination polymers (Al-PCP). By applying the appropriate carbonization temperature, both high surface area and large pore volume are realized for the first time. Our NPC shows much higher porosity than other carbon materials (such as activated carbons and mesoporous carbons). This new type of carbon material exhibits superior sensing capabilities toward toxic aromatic substances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
369
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 608 publications
(380 citation statements)
references
References 57 publications
7
369
0
4
Order By: Relevance
“…CTF-1-200W exhibits a steep rise at a high relative pressure (P/P 0 B 1), indicating macrospores formed between highly aggregated particles, 49 consistent with the low surface area. 50,51 Among all samples, CTF-1-100W has the highest ordered structure both in plane and interlayer. Therefore, the morphology of CTF-1-100W was observed by TEM as shown in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…CTF-1-200W exhibits a steep rise at a high relative pressure (P/P 0 B 1), indicating macrospores formed between highly aggregated particles, 49 consistent with the low surface area. 50,51 Among all samples, CTF-1-100W has the highest ordered structure both in plane and interlayer. Therefore, the morphology of CTF-1-100W was observed by TEM as shown in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…252 Chauvin and co-workers reported LbL assembly with electrochemical oxidation of thiols to produce multilayer assemblies of coordination complexes. 253 Two kinds of complexes bearing two anchoring groups, [Ru(tpySH) 2 ] 2+ and [Fe(tpySH) 2 ] 2+ (tpySH: 4¤-[2-(p-phenoxy)-ethanethiol]-2,2¤:6¤,2¤¤-terpyridine), were used for this assembly. In the initial step, a SAM of these complexes was formed on gold electrodes with the second unreacted thiol moiety exposed at the outer surface.…”
mentioning
confidence: 99%
“…The Cr-MOF derived carbons samples produced at different temperatures MDC-600, MDC-700 and MDC-800 The mass loss observed from the derived carbons from the Cr-MOF (Figure 3a) was relatively lower when compared to that of pristine Cr-MOF and this can be explained by the structural changes that were induced by the carbonisation process. Even though Ming et al [19] had reported that porous carbons obtained from MOFs consisting of metals with higher boiling points than Zn (such as Fe, Co, Cu) could retain the metallic species, and they could be removed from the resulting carbons after being washed with acid [19]. Although as stated, it is evident from this study that Cr oxide and formed carbides were very difficult to be removed and hence Cr-MOF carbonisation is not recommended for this type of MOF.…”
Section: Figure 2: Pxrd and Sem Images Of Cr-mof MDCmentioning
confidence: 99%